3D multi-resolution SPH modeling of the water entry dynamics of free-fall lifeboats. (1st August 2022) - Lyu, Hong-Guan; Sun, Peng-Nan; Miao, Jian-Ming; Zhang, A-Man
Abstract: Lifeboats can be launched through free-fall in extreme maritime accidents to fast leave the hazardous area, which deserves particular attention because it is tightly related to the safety of lifeboats and the carried passengers as well. This paper, within the framework of a fully 3D and multi-resolution Smoothed Particle Hydrodynamics (SPH) model, aims at investigating the water entry dynamics of a free-fall lifeboat with different water entry angles. First of all, two rigorous model validations are performed to demonstrate the accuracy, stability and convergence of the present SPH model. Furthermore, the water entry dynamics of the lifeboat with respect to different water entry angles, including the motion characteristics and cavity evolutions, is investigated and discussed in detail based on the SPH results. It is clearly demonstrated that the present SPH model possesses (1) satisfactory accuracy for predicting the water entry dynamics of a lifeboat, and (2) a better ability to capture the splashing jets and scattering droplets than mesh-based solvers thanks to its entirely Lagrangian nature. In addition, it is also demonstrated that the water entry angle exerts significant effects on the water entry dynamics of a lifeboat, which should be taken into account in the design stage to provide safer productions. Highlights: A multi-resolution and fully 3D SPH model for water entry problems is presented. A simple procedure to generate uniform particles is applied for complex geometries. The present SPH model is shown to be superior in simulating water entry problems. The water entry angle exerts significant effects on lifeboat's water entry dynamics.